Pengaruh E-Service Quality, eWOM , dan Sales Promotion pada saat Special Event Day terhadap Impulse Buying Pengguna Aplikasi Shopee (Studi pada Mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Kudus) (Institut Agama Islam Negeri Kudus, 2023)
AbstractThis research aims to analyze the influence of e-service quality, electronic word of mouth (eWOM), and sales promotion during special event days on impulse buying behavior of Shopee application users among students of the Faculty of Islamic Economics and Business at IAIN Kudus. This study employs a quantitative approach using field research and purposive sampling technique to determine a sample size of 100 respondents. The data is analyzed using multiple regression analysis method with the assistance of SPSS data processing program. The results show that e-service quality, eWOM, and sales promotion individually have a positive and significant effect on impulse buying behavior of Shopee application users during special event days. Based on these findings, it can be concluded that improving e-service quality, utilizing eWOM, and implementing sales promotion during special event days can increase the likelihood of impulse buying behavior among Shopee application users. The practical implications of this research are that sellers and electronic trading platform managers can consider these factors to increase sales through impulse buying.Keywords: e-service quality, electronic word of mouth, sales promotion, special event day, impulse buying, Shopee.Abstrak Penelitian ini bertujuan untuk menganalisis pengaruh e-service quality, electronic word of mouth (eWOM), dan sales promotion pada saat special event day terhadap impulse buying pengguna aplikasi Shopee di kalangan mahasiswa Fakultas Ekonomi dan Bisnis Islam IAIN Kudus. Penelitian ini menggunakan pendekatan kuantitatif dengan jenis penelitian lapangan (field research) dan teknik purposive sampling untuk menentukan sampel penelitian sebanyak 100 responden. Data penelitian dianalisis dengan menggunakan metode analisis regresi berganda dengan bantuan program olah data SPSS. Hasil penelitian menunjukkan bahwa e- service quality, eWOM, dan sales promotion secara parsial atau individual berpengaruh positif dan signifikan terhadap impulse buying pengguna Shopee pada saat special event day. Berdasarkan temuan ini, dapat disimpulkan bahwa peningkatan e-service quality, penggunaan eWOM, dan sales promotion pada saat special event day dapat meningkatkan kemungkinan impulse buying pengguna aplikasi Shopee. Implikasi praktis dari penelitian ini adalah bahwa penjual dan pengelola platform perdagangan elektronik dapat mempertimbangkan faktor-faktor ini untuk meningkatkan jumlah penjualan melalui impulse buying.Kata Kunci: e-service quality, electronic word of mouth, sales promotion, special event day, impulse buying, Shopee.